2003
DOI: 10.1016/s0022-5223(03)00028-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibrosis and lung cancer: risk and benefit analysis of pulmonary resection

Abstract: Patients with pulmonary fibrosis undergoing pulmonary resection for non-small cell lung cancer have increased postoperative morbidity and mortality, but an important subgroup has a good long-term outcome. Postoperative acute respiratory distress syndrome is associated with low preoperative gas transfer and a high composite physiological index. Resection of non-small cell lung cancer is appropriate in pulmonary fibrosis, provided that the level of functional impairment is carefully factored into patient selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 24 publications
(24 reference statements)
1
146
0
3
Order By: Relevance
“…Previous studies [20][21][22][23][24][25] reported that postoperative respiratory complications were found in 26%-54.0% of patients with IPF, moderately higher than in the present study, in which the CPFE group had a significantly higher rate of cardiopulmonary morbidity than the IPF alone group; this was assumed to be due to the fact that postoperative PFT decreased unexpectedly in CPFE, involving both %VC and FEV1%, because the CPFE patients experienced AE at almost the same rate as IPF patients without emphysema and required more HOT than IPF patients without emphysema. Moreover, previous studies 7,9,10,14) noted that CPFE was highly associated with pulmonary hypertension, which might be regarded as a cause of more 19) reported that postoperative pulmonary complications occurred in 20% of CPFE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [20][21][22][23][24][25] reported that postoperative respiratory complications were found in 26%-54.0% of patients with IPF, moderately higher than in the present study, in which the CPFE group had a significantly higher rate of cardiopulmonary morbidity than the IPF alone group; this was assumed to be due to the fact that postoperative PFT decreased unexpectedly in CPFE, involving both %VC and FEV1%, because the CPFE patients experienced AE at almost the same rate as IPF patients without emphysema and required more HOT than IPF patients without emphysema. Moreover, previous studies 7,9,10,14) noted that CPFE was highly associated with pulmonary hypertension, which might be regarded as a cause of more 19) reported that postoperative pulmonary complications occurred in 20% of CPFE patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cancers of lung, liver, and breast are often associated with fibroblast activation, proliferation, and collagen deposition. [3][4][5] Fibroblasts may influence cancer development in different ways. Several factors secreted by fibroblasts, such as epidermal growth factor, hepatocyte growth factor, and interleukin-6 (IL-6), can stimulate cancer cell proliferation and enhance their invasive properties.…”
mentioning
confidence: 99%
“…IP is associated with an increased risk of postoperative acute exacerbation [1]. Acute exacerbation of IP is a serious postoperative complication and the consequences are extremely poor.…”
Section: Discussionmentioning
confidence: 99%